Current Pathogenesis and Treatment of Cutaneous Lupus Erythematosus - Hazlianda, Cut Putri; Diamanda, Ika (CoinReads Media Prima, 2023)
Lupus erythematosus (LE) is a chronic autoimmune illness with a broad range of clinical symptoms. These conditions can range from systemic lupus erythematosus (SLE), which affects different organ systems in the body, to cutaneous lupus erythematosus (CLE), which affects only the skin. The precise pathophysiology of CLE is unknown, although it appears to include a complicated interaction of genetic predisposition and environmental stimuli such as UV light, medications, trauma, and hormones. The emergence of the inflammatory infiltrate seen in CLE lesions has also been documented in several studies; this information is crucial for figuring out which specific inflammatory mediators are responsible for tissue damage. Currently prescribed medications for CLE often include antimalarials, systemic corticosteroids, immunosuppressants, and immunomodulators; cytotoxic drugs are only used in the most severe instances.